2014
DOI: 10.7554/elife.03297
|View full text |Cite
|
Sign up to set email alerts
|

The scaffold protein Nde1 safeguards the brain genome during S phase of early neural progenitor differentiation

Abstract: Successfully completing the S phase of each cell cycle ensures genome integrity. Impediment of DNA replication can lead to DNA damage and genomic disorders. In this study, we show a novel function for NDE1, whose mutations cause brain developmental disorders, in safeguarding the genome through S phase during early steps of neural progenitor fate restrictive differentiation. Nde1 mutant neural progenitors showed catastrophic DNA double strand breaks concurrent with the DNA replication. This evoked DNA damage re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 94 publications
2
59
0
7
Order By: Relevance
“…However, it is possible that FBW7 may regulate the abundance of NDE1 in other phases of the cell cycle, where priming could occur by another kinase. NDE1 has important functions in mitosis (Feng & Walsh, ; Vergnolle & Taylor, ) and S phase (Houlihan & Feng, ), and naturally occurring inactivating mutations in the NDE1 gene in humans result in microcephaly (Alkuraya et al , ; Bakircioglu et al , ), a condition associated with the reduction the neuronal progenitor pool through effects on cell cycle progression and apoptosis. Given the well‐known role of FBW7 as a tumor suppressor (Crusio et al , ; Wang et al , ; Davis et al , ), it is tempting to speculate that an excessive accumulation of NDE1 throughout the cell cycle could contribute to tumorigenesis induced by inactivating mutations in FBXW7 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that FBW7 may regulate the abundance of NDE1 in other phases of the cell cycle, where priming could occur by another kinase. NDE1 has important functions in mitosis (Feng & Walsh, ; Vergnolle & Taylor, ) and S phase (Houlihan & Feng, ), and naturally occurring inactivating mutations in the NDE1 gene in humans result in microcephaly (Alkuraya et al , ; Bakircioglu et al , ), a condition associated with the reduction the neuronal progenitor pool through effects on cell cycle progression and apoptosis. Given the well‐known role of FBW7 as a tumor suppressor (Crusio et al , ; Wang et al , ; Davis et al , ), it is tempting to speculate that an excessive accumulation of NDE1 throughout the cell cycle could contribute to tumorigenesis induced by inactivating mutations in FBXW7 .…”
Section: Discussionmentioning
confidence: 99%
“…Human and mouse studies have shown that diverse mutations including Nde1, Cdk5rap2 and Magoh induce microcephaly through a combination of loss of progenitor self-renewal, premature differentiation, and progenitor apoptosis (Pawlisz et al, 2008;Lizarraga et al, 2010;Silver et al, 2010;Houlihan and Feng, 2014). Mutations of both Nde1 and Cenpj have been shown to induce microcephaly through p53-dependent apoptosis (Bazzi and Anderson, 2014;Houlihan and Feng, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of both Nde1 and Cenpj have been shown to induce microcephaly through p53-dependent apoptosis (Bazzi and Anderson, 2014;Houlihan and Feng, 2014). In all of these examples, the phenotype produced in mice is severe brain malformation.…”
Section: Discussionmentioning
confidence: 99%
“…In an accelerated process, patients with the heritable DNA repair deficiency syndrome Fanconi anemia hyperactivate p53 in response to unresolved DNA damage and eventually experience bone marrow failure owing to progressive HSC loss (Ceccaldi et al, 2012). Excessive p53-dependent apoptosis can also drive developmental disorders of the brain (Houlihan and Feng, 2014) and aging-associated neurodegenerative diseases, namely Alzheimer’s and Parkinson’s diseases (reviewed in Checler and Alves da Costa, 2014). As a regulator of cell death, p53 has been implicated in the pathological response to cerebral and cardiac ischemia; p53 inhibition has been proposed as a protective strategy in the acute phase following injury (Gudkov and Komarova, 2010).…”
Section: The Origins Of P53mentioning
confidence: 99%